2006
DOI: 10.1111/j.1527-5299.2006.05336.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Implications of Anemia in Congestive Heart Failure Patients Followed at a Specialized

Abstract: The objective of this study was to assess the prevalence of anemia and to investigate its association with comorbidities and its impact on clinical outcomes in patients with heart failure. The association of predefined anemia, as well as the correlation of serum hemoglobin level as a continuous variable, with outcomes of emergency department visits, hospitalization, and mortality was investigated. There were fewer anemic patients in New York Heart Association classes I and II than in classes III and IV. Anemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 21 publications
0
13
1
Order By: Relevance
“…In point of fact the present findings, in a relatively large sample of patients with decompensation of CHF, seem to conflict with many previous studies which suggest that anemia strongly and independently predicts mortality in mostly stable CHF patients and preserves or reduces the left ventricular ejection fraction [2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21]. Although this discrepancy could be attributed to the nature of the illness (e.g.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…In point of fact the present findings, in a relatively large sample of patients with decompensation of CHF, seem to conflict with many previous studies which suggest that anemia strongly and independently predicts mortality in mostly stable CHF patients and preserves or reduces the left ventricular ejection fraction [2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21]. Although this discrepancy could be attributed to the nature of the illness (e.g.…”
Section: Discussioncontrasting
confidence: 55%
“…Secondary analyses of randomized trials, by the selection of younger and healthier CHF patients, are not representative of the everyday clinical practice CHF patients in whom noncardiac comorbidities are highly prevalent [15,16,17,18,19,20,21]. On the other hand in some previously published prospective observational studies, in which the included patients were more representative of the everyday clinical practice, only partial adjustment for noncardiac comorbidities was accomplished [12,13,14]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the odds of malnutrition were higher in those who had lower serum hemoglobin level, this is in line with current knowledge [ 3 , 24 , 25 ]. It is well known that anemia has a strong impact on NYHA functional class in heart failure [ 40 ]. A Canadian study identified anemia by itself had a strong impact on clinical outcome of heart failure patients with higher number of anemic patients fitting to a higher functional class of heart failure [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of anemia depends both on the severity of CHF and diagnostic criteria used to define it, but may be as high as 50% in selected patient cohorts (3,6). Of note, anemia is not only prevalent in the CHF population, but several studies in different patient populations found an association with anemia, impaired cardiac function, more health care utilization, and morbidity (1,(7)(8)(9)(10)(11). In addition, numerous studies have assessed associations between anemia and mortality in CHF.…”
mentioning
confidence: 97%